Droplet splashing during arc spraying of steel and the effect on deposit microstructure - Newbery, A; Grant, P (ASM International, 2000)
The mechanism by which droplet deposition occurs is important when filling substrate features for the electric arc spray forming of steel tooling. Particle image velocimetry and high-speed video imaging techniques have been used to observe droplet deposition, particularly with regard to the behavior of droplets originating from splashing. Droplet splashing on deposition has been seen to be significant, and splash droplets form a large proportion of the overspray. The splash droplets are smaller and, when first created, move slower than the parent droplet. When spraying into deep features, the lateral and upward movement of splash droplets acts as a mechanism for deposit formation onto surfaces in shadow from the main spray. Microstructural study has shown that oxidation of the splash droplets before redeposition leads to a deposit with a high fraction of oxide. Simultaneous growth of deposit formed directly from the spray, and from splash droplets, results in a banded microstructure containing elongated macropores. A mechanism for such microstructural evolution is proposed.